The Influence of E-Service Quality, E-Wom and Discounts on Transportation Ticket Purchase Decisions or Accommodation Booking Services on Traveloka Users - Dewantra, Nicholas Naufal; Sukarno, Agus; Oetomo, Hadi (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
The development of the world of information and communication technology (ICT) has brought profound changes to various aspects of human life. These changes are not only limited to the way we communicate or access information, but also include major transformations in industry and other economic sectors. One sector that has been greatly affected by ICT advancements is transportation, tourism and hospitality. These industries are experiencing drastic changes in the way services are delivered and received by consumers.This study aims to analyze the effect of E-Service Quality, E-Wom and Discounts on Purchasing Decisions on transportation and accommodation for traveloka customers. The sample population in this study were all traveloka customers with purposive sampling method by distributing questionnaires online and offline by utilizing google form and managed to get 109 respondents. The analytical methods used in this study are validity test, reliability test, multiple linear regression analysis, hypothesis testing consisting of f test and t test, and the coefficient of determination using SPSS 30 software. This study concludes that E-Service Quality and Discounts have a positive and significant effect on traveloka consumer purchasing decisions. Meanwhile, E-WOM has no significant effect on traveloka consumer purchasing decisions.